The increasing presence of large firms and its consequences for US startup rates - Niklas Garnadt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
While the significant decline in US startup rates over the past 30 years has raised concern about the health of the US economy its causes have not yet been fully understood. I document the concurrent increase in the size and presence of large firms in the US economy and link it to the decline in firm creation rates. I construct a simple model that rationalizes this channel by increases in the span of control of managers.
Keywords: E24; L25; L26; 330